Krishna Sobti's Views on Literature and the Poetics of Writing Theoretical Positions and Literary Practice in Modern Hindi Literature - Vuille, Rosine-Alice (Welten Süd- und Zentralasiens / Worlds of South and Inner Asia / Mondes de l'Asie du Sud et de l'Asie Centrale, 2022)
The Hindi writer Krishna Sobti (1925-2019) carved out a special place for herself within the post-Partition Hindi literary sphere thanks to her idiosyncratic use of language and her bold choices of topics. Known primarily as a novelist, she is also the author of essays and other non-fictional texts. Focusing on the main themes of Sobti's oeuvre, this study analyses the relationship between her views on poetics and her own literary practice.